PENGALAMAN MAHASISWA DALAM PROSES BELAJAR-MENGAJAR DI DALAM RUANG: SEBUAH KAJIAN FENOMENOLOGIS - Sumartono, Mr. (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2008)
eaching-learning process is not a linear sequence of events but a dynamic phenomenon. In a higher educational institution such as the Department of Art, Institut Seni Indonesia (Indonesia Institute of the Arts) Yogyakarta, lecturers deliver knowledge to students and at the same time the students get interesting, often unthinkable. experience unrealized by them. This research deals with such an issue. Analyzed phenomenologically, the experience of the students attending theoretical and practical classes at this institution will reveal a lot of often unthinkable meanings.Keywords: phenomenology, experience, geometric space, lived space.